Model-driven design using IEC 61499 : a synchronous approach for embedded and automation systems /: a synchronous approach for embedded and automation systems. ([2014]) - Yoong, Li Hsien; Roop, Partha S; Bhatti, Zeeshan E; Kuo, Matthew M. Y
No abstract available